PENERAPAN MANAJEMEN RESIKO TERHADAP KEDATANGAN KAPAL PENUMPANG PT PELNI CABANG TANJUNG PRIOK - Aji Pandita Ratu Rukmantara (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
The objective of this research is to analyze the implementation of risk management in the arrival of passenger ships at PT PELNI Tanjung Priok Branch. This research method uses qualitative descriptive with data collection techniques through interviews and field observations. The research findings indicate that there are potential risks that may occur at PT PELNI Tanjung Priok Branch, and there are risk controls that can be implemented to minimize the possibility of risks occurring. Keywords: Risk Management, PT PELNI Tanjung Priok Branch, Passenger Ships